Identifying and Prioritizing the Basis of Entrepreneurial University Using Meta-Synthesis and Group Analytic Hierarchy Process for Iranian Universities - Ali Akbar Akbari; sayed jalal musavi; Hamidreza esmaely Givi (پژوهش در نظام‌های آموزشی, 2020)
The purpose of this study is to identify and prioritize the components of the entrepreneurial university. In this research, in order to summarize and aggregate the findings of previous researches, the meta-synthesis method has been used. First, by searching in various scientific documents databases, 842 primary sources, some of which were referred to the entrepreneurial university (third generation university), were extracted. Then, considering the relevance to the research, the initial sources were seived and 75 sources were selected for the final consideration. Subsequently, by using content analysis and open and axial coding of selected resources, 20 factors were identified in five main categories 1- Strategy and leadership, 2- Structure and processes, 3- Culture, 4- Education system and 5- Network of relationships  as the main components and categories of the formation of an entrepreneurial university. Finally, the weight and priority of these components as inputs of policy making in the field of higher education to push the universities of the country towards the entrepreneurial university, is calculated and presented using the group analytic hierarchy process and judgments of seven experts in the field of higher education.  Accordingly, the five components of leadership, organization, resource management, entrepreneurial attitudes, and laws are of the highest importance. By the end, to facilitate transition to the entrepreneurial university some suggestions were presented regarding important components.